The cancer-associated fibroblasts interact with malignant T cells in mycosis fungoides and promote the disease progression - Yige Zhao; Yong Li; Yong Li; Panpan Wang; Mengyan Zhu; Jiaqi Wang; Bo Xie; Chenyu Tang; Yangyang Ma; Shiwen Wang; Sha Jin; Jinhui Xu; et al. (Frontiers in Immunology)
BackgroundCutaneous T-cell lymphoma (CTCL) is a heterogeneous group of T-cell lymphomas characterized with the presence of clonal malignant T cells. Mycosis fungoides (MF) is the most common type of CTCL. However, the pathogenesis of MF and the role of the tumor microenvironment (TME) remain unclear.MethodsWe performed single-cell RNA sequencing on tumor and adjacent normal tissues and peripheral blood mononuclear cell (PBMC) from patients with advanced MF and healthy control (HC). We compared skin lesions in different stages within the same patient to overcome inter-individual variability.ResultsThe malignant clones displayed dual phenotypes characterized with tissue-resident memory T cells (TRMs) and central memory T cells (TCMs). We supposed that the tumor cells transformed from TRM-dominant phenotype to TCM-dominant phenotype during MF progressed from early-stage to advanced-stage. The cancer-associated fibroblasts (CAFs) showed active role in TME. The occurrence of inflammatory CAFs (iCAFs) may represent the advanced-stage MF. There may be mutual positive feedback of the crosstalk between tumor cells and CAFs during the MF development. Tumor cells promote CAF generation, and the CAFs, in turn, improve the invasiveness and metastasis of the malignant T cells through the IL-6/JAK2/STAT3/SOX4 or IL-6/HIF-1α/SOX4 pathway. SOX4 may be a critical regulatory gene of this positive feedback loop. Target SOX4 may disrupt the interactions between tumor cells and CAFs.ConclusionOur study revealed the origin and evolution trajectory of MF and uncovered the intercellular interactions between malignant T cells and CAFs, providing new insights into the novel treatment targets of MF.